Inhibition of Listeria monocytogenes by fatty acids and monoglycerides. - Wang, L L (1992)
Fatty acids and monoglycerides were evaluated in brain heart infusion broth and in milk for antimicrobial activity against the Scott A strain of Listeria monocytogenes. C12:0, C18:3, and glyceryl monolaurate (monolaurin) had the strongest activity in brain heart infusion broth and were bactericidal at 10 to 20 micrograms/ml, whereas potassium (K)-conjugated linoleic acids and C18:2 were bactericidal at 50 to 200 micrograms/ml. C14:0, C16:0, C18:0, C18:1, glyceryl monomyristate, and glyceryl monopalmitate were not inhibitory at 200 micrograms/ml. The bactericidal activity in brain heart infusion broth was higher at pH 5 than at pH 6. In whole milk and skim milk, K-conjugated linoleic acid was bacteriostatic and prolonged the lag phase especially at 4 degrees C. Monolaurin inactivated L. monocytogenes in skim milk at 4 degrees C, but was less inhibitory at 23 degrees C. Monolaurin did not inhibit L. monocytogenes in whole milk because of the higher fat content. Other fatty acids tested were not effective in whole or skim milk. Our results suggest that K-conjugated linoleic acids or monolaurin could be used as an inhibitory agent against L. monocytogenes in dairy foods.